"Psychoanalysis and Ethnology" Revisited: Foucault's Historicization of History. (September 2017) - Allen, Amy
Abstract: This article re‐examines the closing sections of Michel Foucault's The Order of Things in order to address the longstanding question of whether he is best understood as a philosopher or a historian. My central argument is that this question misses the crucial point of Foucault's work, which is to historicize the notion of history (as it is traditionally understood, represented by History with a capital H), which Foucault takes to be central to the historical a priori of modernity. An examination of his historicization of History thus reveals that Foucault is neither simply a philosopher—because he conceives of philosophy in modernity as a historical enterprise—nor a historian—because his own historical approach is designed to transform the modern historical a priori from within. This analysis also sheds new light of Foucault's relationship to psychoanalysis and his conception of critique.